Enhancement of thermal stability, strength and extensibility of lipid-based polyurethanes with cellulose-based nanofibers - Floros, Michael; Hojabri, Leila; Abraham, Eldho; Jose, Jesmy; Thomas, Sabu; Pothan, Laly; Leão, Alcides Lopes [UNESP]; Narine, Suresh (Elsevier B.V., 2012)
Cellulose was extracted from lignocellulosic fibers and nanocrystalline cellulose (NC) prepared by alkali treatment of the fiber, steam explosion of the mercerized fiber, bleaching of the steam exploded fiber and finally acid treatment by 5% oxalic acid followed again by steam explosion. The average length and diameter of the NC were between 200-250 nm and 4-5 nm, respectively, in a monodisperse distribution. Different concentrations of the NC (0.1, 0.5, 1.0, 1.5, 2.0 and 2.5% by weight) were dispersed non-covalently into a completely bio-based thermoplastic polyurethane (TPU) derived entirely from oleic acid. The physical properties of the TPU nanocomposites were assessed by Fourier Transform Infra-Red spectroscopy (FTIR), Thermo-Gravimetric Analysis (TGA), Differential Scanning Calorimetry (DSC), X-Ray Diffraction (XRD), Dynamic Mechanical Analysis (DMA) and Mechanical Properties Analysis. The nanocomposites demonstrated enhanced stress and elongation at break and improved thermal stability compared to the neat TPU. The best results were obtained with 0.5% of NC in the TPU. The elongation at break of this sample was improved from 178% to 269% and its stress at break from 29.3 to 40.5 MPa. In this and all other samples the glass transition temperature, melting temperature and crystallization behavior were essentially unaffected. This finding suggests a potential method of increasing the strength and the elongation at break of typically brittle and weak lipid-based TPUs without alteration of the other physico-chemical properties of the polymer. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Nanocellulose; Nanocomposites; Polyurethanes; Mechanical properties; Biomaterials; Renewable resources